VALUE OF ULTRASOUND IN THE DIAGNOSIS OF PROSTATE CANCER IN PATIENTS AGED 50 YEARS AND OLDER AT MEDIC MEDICAL CENTER, 2020–2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the diagnostic performance of transrectal ultrasound (TRUS) features in detecting prostate cancer in men aged ≥50 years at Medic Medical Center from 2020–2023.Methods: A retrospective cross-sectional study was conducted on 583 medical records of men aged ≥50 years who were suspected of having prostate cancer based on abnormal digital rectal examination (DRE) findings or prostate-specific antigen (PSA) levels ≥4 ng/mL at Medic Medical Center from January 2020 to April 2023.Results: The prevalence of prostate cancer in high-risk individuals was 39.8%. TRUS features, including abnormal nodules and heterogeneous echogenicity, showed the strongest associations with prostate cancer, with sensitivities of 91.8% and 91.4%, respectively, and a specificity of 83.2% for both. The multivariate regression model demonstrated excellent diagnostic performance (AUC = 0.921). Risk stratification combining abnormal nodules, irregular prostate capsule, and increased vascularity achieved a diagnostic accuracy of 95.4%.Conclusion: TRUS demonstrates high diagnostic value for prostate cancer in high-risk individuals through a multivariate regression model with an AUC of 0.921. These findings confirm the important role of TRUS in risk stratification and in guiding prostate biopsy indications.
Keywords: Prostate cancer; Prostate gland; Transrectal ultrasound; TRUS.